Anaerobic co-composting of sugarbeet waste and wine factory wastes - Ipek, U; Öbek, E; Akça, L; Arslan, EI; Hasar, H (Parlar Research & Technology Ug, 2001)
The present research deals with evaluation of the efficiency of an anaerobic batch composting system to produce a product safe to use from a hygienic standpoint. So, using bacteriological parameters as a guideline, faecal coliforms (FC) and total coliforms (TC) on raw waste, leachates and finished compost were determined. Measurements also include total solids (TS), volatile solids (VS), pH, conductivity, chemical oxygen demand (COD), total Kjeldahl nitrogen (TKN), ammonium, total phosphorus (TP) and alkalinity in the leachate. Determinations on some metals, VS, cellulose, pH, conductivity, moisture, C, N, S, Ca, Mg, Na and K were carried out in the starting mixture and the compost obtained. The mixture of the composting materials was as follows: 70% wine factory wastes, 20% sugarbeet waste and 10% biological treatment sludge. By the end of the composting process (day 108), the TC and FC numbers in co-compost were reduced from 1609. 10(4) and 918. 10(4) MPN/g.ww to 0.33. 10(4) and 0.16.10(4) MPN/g.ww, respectively. Although FC and TC numbers were not completely eliminated in both leachate and compost at the end of the composting, their levels were very low. The fact that pathogen die-off is faster than that of the indicator organisms suggests that low numbers of indicator organisms are sign of elimination of pathogens.
Keywords: anaerobic co-composting; sugarbeet waste; wine factory wastes; biological treatment sludge; faecal coliforms; total coliforms